Identification of the Microbial Consortium in Sri Lankan Buffalo Milk Curd and their growth in the Presence of Prebiotics - Dekumpitiya, N.; Gamlakshe, D.; Abeygunawardena, S. I.; Jayaratne, D. (Journal of Food Science and Technology Nepal, 2016)
The production and consumption of traditionally fermented buffalo milk curd provides many economical and food security benefits to both producers and consumers in the country. To improve this traditional product as a value-added product, an investigation was conducted to elucidate the microbial consortium associated with curd using culturable techniques and the microbial load was quantified in the presence of prebiotics. Twenty six samples of curd were analyzed to isolate microorganisms. The two major LAB groups present in the samples were characterized as Lactobacillus and Streptococcus. LABs were further identified as Lactobacillus delbrueckii subsp. lactis, L. planatarum, L. helviticus, Lactobacillus delbrueckii subsp. bulgaricus and L. casei subsp casei, Streptococcus thermophiles and S. lactis. Saccharomyces cerevisiae, Micrococcus spp., and Bacillus spp. were also present in this microbial consortium The addition of two types of commercially available prebiotics improved the counts of Lactobacillus in curd samples, despite the difference in the prebiotic compounds.